Not everything is as it seems: a rare form of metastatic breast cancer - Mariana Rocha; Daniela Azevedo; António Teira; Miguel Barbosa (University of São Paulo, 2019)
Breast cancer is the most prevalent cancer and the leading cause of cancer-related death among females worldwide. Despite all therapeutic advances, metastatic breast cancer is still associated with a median overall survival of 3 years. Alongside this condition, bladder metastases of solid neoplasms are rarely observed. In this setting, the secondary bladder tumors with an origin in breast cancer occur in 2.5% of cases in some series. The authors report the case of a 68-year-old female with stage IV breast cancer (bone metastasis) treated with anastrozole, who presented with peripheral edema and renal failure with a creatinine clearance of 12.5 mL/min. After hospital admission, the patient was diagnosed with new liver lesions and bladder involvement with bilateral hydronephrosis. She was submitted to bilateral percutaneous nephrostomies with improvement in renal function. There was a high suspicion of primary bladder tumor in this patient who was a previous smoker, with a family history of high-grade bladder carcinoma (her mother). Liver and transurethral biopsies were performed, and histological examination was consistent with breast cancer metastases. The patient started treatment with capecitabine and denosumab, remaining clinically stable after 3 months of treatment. This case report underlines the diagnostic challenges of bladder metastases in a patient with multiple risk factors for bladder cancer and without evident clinical symptoms. Even though this is a rare entity, the close surveillance of metastatic breast cancer is important in order to allow early detection of new metastatic sites and their treatment to preserve the quality of life in these patients.